Los imaginarios disruptivos del cuerpo queer: un análisis de la masculinidad disidente en la ilustración mexicana del siglo XXI - Trejo Olvera, Luis Nivardo; Ruiz Tresgallo, Silvia (El Colegio de México A.C., 2021)
The cultural production of online images in Mexico includes the work of artists proposing dissident representations of masculinity dissenting. The illustrators Felix d'Eon, Fabián Cháirez, Wonkamon, and Pierna Cruzada challenge traditional representations of hegemonic masculinity in national culture by including homosexual desire, feminized bodies, and ethnic diversity within male representations. This essay posits a deconstructive queer view of national identity politics. Our visual literacy methodology—given the free availability of these images online—seeks to give visibility to mechanisms of contemporary queer representation as well as their political potential.